Case Report Tuberculosis of The Prostate: Findings of Post Transurethral Resection of Prostate (TURP) Procedure - Kadek Mien Dwi Cahyani; Ni Made Dwita Yaniswari; Novitasari Novitasari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Prostate tuberculosis (PTB) is one of extra pulmonary tuberculosis which potentially has more frequent fatal complications and more severe quality of life deterioration. It is a very rare disease, with prevalence of 2.6% of all urogenital tuberculosis (UGTB). Prostate tuberculosis may be a sexually transmitted disease and leads to sexual dysfunction. Case: Male, 54 years old, with urinary retention, dysuria, flank pain in the last 1-month, recurrent urinary tract infection in the past 1 year and decrease body weight of 8 kg in 1 month. Physical examination demonstrates enlarged prostate. Patient was referred to Wangaya Hospital with benign prostate hyperplasia (BPH) and suspect malignancy. After underwent clinical and supporting examination, patient underwent TURP procedure. Histopathology examination revealed PTB. Patient was then treated with first line anti-tuberculosis drug (ATD). Discussion: Multiple risk factors are involved in TB disease. PTB spread occur through hematogenous, lymphatic, or direct routes. Clinical features and supporting examinations of PTB are non-specific. Diagnosis often made through incidental histology finding post TURP. Standard ATD regiment administered based on World Health Organization (WHO) guideline. Duration can be prolonged due to suboptimal concentration to prostate tissue. Conclusion: Multidisciplinary approach for extra pulmonary TB is needed. Thorough history taking, and high index of suspicion are important aspects. PTB diagnosis should be considered in patients with recurrent lower urinary tract symptoms refractory to standard therapy in TB endemic area.